2019
DOI: 10.1093/tas/txz121
|View full text |Cite
|
Sign up to set email alerts
|

Alkali addition and roughage inclusion effect on performance and carcass characteristics of feedlot steers fed diets containing 60% dried distillers grains with solubles

Abstract: Three experiments were conducted to determine the effectiveness of calcium hydroxide (Ca(OH)2) addition and roughage inclusion on digestibility, performance, and carcass characteristics of steers fed 60% dried distillers grains with solubles (DGS). Statistical analyses for studies were conducted using the MIXED procedures of SAS. In experiment 1, 48 steers (353.5 ± 7.55 kg) were allotted to individual pens and fed 1 of 3 diets (dry matter [DM] basis) containing 60% dried DGS, 20% corn silage, and 4% supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Addition of hydrolytic chemical agents, such as CaO, to highly lignified feedstuffs have been shown to break bonds between lignin and structural carbohydrates, resulting in increased microbial fermentation of the feedstuff ( Jung and Deetz, 1993 ). Although the roughages in the present study were not pretreated with a strong base, increases in apparent digestibilities of DM, OM, NDF, and ADF from direct addition of CaO to rations in the current study aligns with previous research ( Nuñez et al, 2014 ; Lancaster et al, 2019 ). Improved fiber digestibility from direct addition of alkali to rations may occur through degradation of the linkages between lignin and hemicellulose in addition to increased ruminal pH ( Nuñez et al, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Addition of hydrolytic chemical agents, such as CaO, to highly lignified feedstuffs have been shown to break bonds between lignin and structural carbohydrates, resulting in increased microbial fermentation of the feedstuff ( Jung and Deetz, 1993 ). Although the roughages in the present study were not pretreated with a strong base, increases in apparent digestibilities of DM, OM, NDF, and ADF from direct addition of CaO to rations in the current study aligns with previous research ( Nuñez et al, 2014 ; Lancaster et al, 2019 ). Improved fiber digestibility from direct addition of alkali to rations may occur through degradation of the linkages between lignin and hemicellulose in addition to increased ruminal pH ( Nuñez et al, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our data suggest that CaO increased k d in SBH diets, but decreased k d in SBH free diets. Lancaster et al (2019) observed that Ca(OH) 2 increased k d in 60% DDGS diets that contained corn silage, stover, or additional corn. Previous work suggests that high-fiber energy feeds like SBH to diets can decrease rates of degradation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations